FORMULATION AND EVALUATION OF ZOLPIDEM TARTRATE LAYERED TABLETS BY MELT GRANULATION TECHNIQUE FOR TREATMENT OF INSOMNIA - Sri A, Ramya; K, Latha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of this study was to formulate and evaluate the sustained release matrix tablets of zolpidem tartrate, using hydrogenated vegetable oil as a polymer. Methods: Various formulations were prepared by melt granulation method using concentrations Lubritab, HPMC K100, and lactose monohydrate. The optimized formulations were prepared as three-layered tablets using HPMC K4M. Results: All formulations blend were evaluated for various precompression parameters were found to be good. The drug and excipients compatibility study was performed, and the study revealed that there was no interaction between drug and excipients. The compressed tablets were evaluated for various physicochemical parameters. The initial release from the matrix tablet was higher which was reduced by the preparation of three-layered tablet using HPMC K4M. The initial release was controlled to 10–12%, but the complete release was not there in 12 h. To get the complete release of the drug pore forming agent such as lactose and HPMC K100 was included in the matrix. ZT22 and ZT25 were considered as optimized formulations, and the drug release at 12th h is 98.85% and 98.3% respectively. The optimized formulation was subjected to stability studies for 3 months as per ICH guidelines for climate zone III and was found to be stable. Conclusion: Difficulties with sleep onset and or sleep maintenance can be treated successfully using the optimized formulations ZT22 and ZT25 for the prompt onset of action of the drug over a prolonged period of time which may lead to improved efficacy, better patient compliance.